Mitoxantrone-loaded superparamagnetic iron oxide nanoparticles as drug carriers for cancer therapy: Uptake and toxicity in primary human tubular epithelial cells - Cicha, Iwona; Scheffler, Laura; Ebenau, Astrid; Lyer, Stefan; Alexiou, Christoph; Goppelt-Strübe, Margarete (Nanotoxicology, 2016)
Superparamagnetic iron oxide nanoparticles (SPIONs) are in use for many clinical diagnostic and experimental therapeutic applications, for example, for targeted drug delivery. To analyze the cellular responses to mitoxantrone-carrying SPIONs (SPION-MTO), and to the drug released from SPIONs, we used an in vitro system that allows comparison of primary human cells with different endocytotic capacities, namely, epithelial cells from proximal and distal parts of the nephron. SPIONs were selectively and rapidly internalized by proximal tubular cells with high endocytotic potential, but not by distal tubular cells. Uptake did not affect cell viability or morphology. In both cell types, free MTO (10-100 nM) induced double-strand DNA breaks and senescence, cell hypertrophy and reduced cell proliferation. However, cadherin-mediated cell-cell adhesion, cytoskeletal structures or polarity of the cells were not affected. Interestingly, a comparable response was also observed upon treatment with SPION-MTO and was independent of uptake of the particles. The effect of SPION-MTO on cells which did not internalize particles was primarily related to the release of MTO from drug-coated particles upon incubation in serum-containing cell growth medium. In conclusion, we show that whereas the uptake of SPIONs does not affect cellular functions or viability, the toxicity of drug-loaded SPIONs depends essentially on the type of drug bound to nanoparticles. Due to the relatively low systemic toxicity of MTO, the effects of MTO-SPIONs on human tubular cells were moderate, but they may become clinically relevant when more nephrotoxic drugs are bound to SPIONs.
EVALuna2:3835